Survival Analysis of Clinicopathology Profile, Risk Factor, and Prognostic Factor in Cervical Carcinomas with Chemoradiation - Yahya Irwanto; Ineke Permatasari; Aliesya Patricia; Ainun Ganisia; Eviana Norahmawati (Universitas Aisyah Pringsewu, 2022)
Cervical carcinoma causes several problems like pain and suffering at least death. However, it is the most preventable, curable, and high survival type of cancer. This study aims to analyze the survival of cervical cancer patients based on factors that are considered influential, such as clinicopathological profiles, risk factors, and prognostic factors to order the effectiveness of therapy and improve the quality of life in patients receiving chemoradiation. In an analytical observational retrospective cohort design study, using secondary data, samples contain all patients diagnosed with cervical cancer who received chemoradiation therapy from January to December 2017 which is 151 patients. This study revealed that the 5year survival rate is 57.6%. The lowest Person Time is 3 months and the longest is 60 months, average 45.80 months, standard deviation 18.179 months. There was a significant influence on the clinicopathological profile including Age (0.002), Histopathology (0.012), and Stage (0.000). Risk factors: parity (0.000), Education (0.007), Number of Marriages (0.025), Menstrual Disorders (0.021), Contraception (0.004), Cancer History (0.000), Body Mass Index (0.022), Area of residence (0.009). Prognostic factors: chemoradiation type (0.002), chemotherapy type (0.000), radiation type (0.001), radiation technique (0.007). The results indicate that the survival rate of cervical cancer patients with chemoradiation still has to be concern. Abstrak: Karsinoma serviks menyebabkan masalah kesakitan, penderitaan dan menjadi penyebab kematian. Akan tetapi, juga merupakan jenis kanker yang paling dapat dicegah, disembuhkan dan memiliki kesintasan hidup tinggi. Penelitian ini bertujuan untuk menganalisa kesintasan hidup pasien karsinoma serviks berdasarkan faktor yang dinilai berpengaruh yaitu profil klinikopatologi, faktor risiko, dan faktor prognostik guna menilai efektivitas terapi demi peningkatan kualitas hidup pada pasien yang menerima kemoradiasi. Penelitian ini merupakan studi analisis observasional dengan desain retrospective cohort, menggunakan data sekunder, sampel dalam penelitian ini mencakup semua pasien dengan diagnosa karsinoma serviks yang menerima terapi kemoradiasi dari bulan Januari hingga Desember 2017 sejumlah 151 pasien. Pada penelitian ini didapatkan data 5 tahun kesintasan sebesar 57.6%. Person Time terendah 3 bulan dan terlama 60 bulan dengan nilai rata-rata 45,80 bulan, standar deviasi 18,179 bulan. Terdapat pengaruh signifikan Profil Klinikopatologi meliputi kategori Usia (0.002), Histopatologi (0.012), Stadium (0.000). Faktor Risiko meliputi kategori paritas (0.000), Pendidikan (0.007), Jumlah Pernikahan (0.025), Gangguan Menstruasi (0.021), Kontrasepsi (0.004), Riwayat Kanker (0.000), Indeks Masa Tubuh (0.022), Daerah tinggal (0.009). Faktor Prognostik meliputi Jenis Kemoradiasi (0.002), Jenis Kemoterapi (0.000), Jenis Radiasi (0.001), Teknik Radiasi (0.007). Hasil ini menunjukan bahwa kesintasan hidup pada pasien karsinoma serviks yang mendapat terapi kemoradiasi masih membutuhkan perhatian.